HOLLOW FIBER MEMBRANE CHARACTERISTICS AS FILTRATION MEDIA IN LIQUID WASTE PROCESSING WITH ACTIVATED MUD - Endah Palupi, Aisyah (Jurnal Teknik Kimia, 2011)
Application of submerged membrane bioreactor (BRMt) has advantages over external BRMin the treatment of domestic wastewater, namely in terms of operating energy and membranefouling BRMt proper tank design can minimize fouling and extend the operating time of themembrane. Installation bafel can create a circulation flow of water between the wall andmembrane bioreactor (water lift-type reactor). It is intended to create the shear velocity (shearrate) is high on the membrane surface so that the pile of material on the membrane apart andlowering the hydraulic resistance of fouling layer. Flux on the external BRM BRMt and reachedsteady state, takes less than 60 minutes. This was achieved at 0.1333 bar TMP which is also thebest operating pressure on BRMt, while the optimum TMP on external BRM obtained at 1.45 bar.To obtain a high flux and stable in the long term, the operation of the membrane at BRMt usingaeration rate 12 l / minute with a close distance baffle membranes or 7.5 cm from the wall of thetank to increase the shear rate can reduce the occurrence of fouling.Key words: BRMt, bafel, shear rate, MLSS, filtration